Comparative transcriptome analysis reveals abscisic acid-induced bHLH transcription factors involved in saikosaponin biosynthesis in Bupleurum chinense DC - Han Wang; Shanqun Hu; Tong Li; Xuejie Qu; Jiaqi Zhang; Baoshun Wang; Yixuan Sun; Rui Cao; Yutong Yan; Ze Song; Xia’nan Zhang; Rong Luo; et al. (Plant Signaling & Behavior)
Bupleurum chinense DC. a medicinal plant valued for saikosaponins (SSs) with antipyretic and hepatoprotective properties, faces constrained SS biosynthesis mediated by abscisic acid (ABA) during growth. Basic helix-loop-helix (bHLH) transcription factors (TFs) are hypothesized to participate in ABA signaling cascades, but their mechanistic role in SS regulation remains undefined. In this study, 20 differentially expressed BcbHLH genes were identified by transcriptomic profiling of ABA-induced hairy roots, with four MYC-family candidates (BcbHLH1-BcbHLH4) demonstrating ABA-responsive regulatory potential. ABA exposure (100 or 200 μmol/L, 24–72 h) induced dose-dependent SS reduction, while correlation analyses revealed coordinated expression between BcbHLH1-BcHMGR (r = 0.62) and BcbHLH4-BcBAS (r = 0.78), pinpointing these TFs as critical nodes in SS pathway modulation. Tissue-specific profiling showed predominant BcbHLH expression in stems and young leaves, with nuclear localization confirming their transcriptional regulatory organelles. BcbHLH3/4 exhibited transcriptional activation activity in the MYC_N domain, while molecular docking predicted 11th Arginine in the HLH domain as essential for G-box DNA binding. Collectively, our findings suggest that BcbHLH1-BcbHLH4 may serve as potential switches for fine-tuning ABA responsiveness in SS biosynthesis. Strategic manipulation of BcbHLH activity through genetic engineering approaches such as CRISPR-based editing or overexpression could alleviate ABA-mediated biosynthetic repression. Furthermore, precision engineering of the critical functional domain in BcbHLH could enhance promoter-binding activity to target genes and improve SS biosynthesis efficiency. These findings provide a reference framework for harnessing transcriptional regulators to optimize SS production in Bupleurum chinense DC.